OP16 Associations of cholesterol targets and mortality with statin adherence in NHS greater glasgow & clyde's post myocardial infarction population. (3rd September 2019) - Brown, R; Wild, S; Lewsey, J; Welsh, P; Logue, J
Abstract : Background: Under SIGN cardiovascular disease guidelines (2007, 2017), patients >40 years in Scotland are classified as being at high or low risk of a CVD event in the next ten years, with secondary prevention patients automatically considered high risk. The guidelines in Scotland, and elsewhere, state that statins should be offered in secondary prevention regardless of their plasma lipid concentration and that annual monitoring of lipid concentration represents good practice. This descriptive analysis investigated the demographics of a secondary prevention population, their estimated adherence to statin medication and whether targets for cholesterol reduction were achieved. Methods: Data was extracted from the NHS Greater Glasgow and Clyde (NHS GGC) Safe Haven for all patients with a record of a non-fatal myocardial infarction (MI) occurring between 1st March 2008 and 1st March 2014, together with their demographics, lipid concentrations, and statin dispensing records up to 1st March 2017. Estimated adherence for each year post MI was calculated from the dispensing records using the Medication Possession Ratio (MPR) and averaged across the years available for each patient. Descriptive statistics were presented using raw counts and percentages, and means and standard deviations, for categorical and continuous variables respectively. Logistic regression examined associations between adherence and cholesterol targets, and adherence and mortality, and were also adjusted for age, sex, year of MI and deprivation quintile, with results presented as odds ratios (OR). Results: In the population, 11, 568 patients had a previous non-fatal MI, and were predominantly male (7, 002, 60.5%), had a mean age at admission of 66.9 years (SD: 13.9), and approximately a third died before 1st March 2017 (4, 053, 35.0%). 10, 469 patients had at least one year's follow-up allowing average adherence to be estimated and one third (3, 360, 32.1%) had an average statin adherence <80%. Patients with <80% adherence were associated with lower odds of achieving target 40% non-HDL reduction (OR: 0.387 [95% CI: 0.336, 0.446]), which were unaltered after adjustment (OR 0.392 [95% CI: 0.339, 0.452]). These patients were also associated with higher odds of mortality (OR: 1.717 [95% CI: 1.571, 1.877]), with some attenuation following adjustment (OR: 1.653 [95% CI: 1.486, 1.839]). Conclusion: In the NHS GGC post MI population, patients with lower statin adherence were associated with lower odds of achieving cholesterol targets set by current guidelines and higher odds of mortality. However, a large proportion of patients achieved targets and had excellent adherence, questioning the need for regular lipid monitoring.